Microsurgically aided upper lip replantation – case report and literature review. Issue 1 (1st January 2016) - Gustafsson, Jonas; Lidén, Mattias; Thorarinsson, Andri
Abstract: A case with a patient who suffered an upper lip amputation and a lower lip laceration due to dog bite is presented. The amputated segment was replanted using microsurgical technique. The operative technique and postoperative care is presented, as well as a review of the current literature on the subject.